Biogenesis, Trafficking, and Function of Small RNAs in Plants - Tang, Yunjia; Yan, Xiaoning; Gu, Chenxian; Yuan, Xiaofeng (Frontiers in Plant Science, 2022)
Small RNAs (sRNAs) encoded by plant genomes have received widespread attention because they can affect multiple biological processes. Different sRNAs that are synthesized in plant cells can move throughout the plants, transport to plant pathogens via extracellular vesicles (EVs) and transfer to mammals via food. Small RNAs function at the target sites through DNA methylation, RNA interference and translational repression. In this article, we reviewed the systematic processes of sRNA biogenesis, trafficking, and the underlying mechanisms of its functions.